2022
DOI: 10.1021/acs.langmuir.2c01720
|View full text |Cite
|
Sign up to set email alerts
|

Immobilizing Ionic Liquids onto Functionalized Surfaces for Sensing Volatile Organic Compounds

Abstract: Herein, a highly sensitive volatile organic compound (VOC) gas sensor is demonstrated using immobilized ionic liquid (IL), 1-butyl-3-methylimidazolium hexafluorophosphate, onto surfaces functionalized by the quaternary ammonium group −N+R, −COOH, and −NH2, i.e., N+–IL, COOH–IL, and NH2–IL, respectively. These functional groups ensure highly tunable interactions between the IL and surfaces, efficiently modulating the electrical resistance of the immobilized IL upon exposure to acetone and toluene. The immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
(138 reference statements)
0
9
0
Order By: Relevance
“…The third layer on the Au–NH 2 surface is also composed of the “cation–anion” pairs and so on. The difference in cation and anion layers formed closest to the Au–COOH and Au–NH 2 surfaces is due to their completely different interaction energies: the cation–COOH interaction energy is stronger than cation–NH 2 , while that is weaker for anion–COOH than anion–NH 2 . Note that due to the existence of these −COOH and −NH 2 functional groups, the detected ion layering thickness of the IL from the force–distance curves is not exactly equal to but very close to the theoretical cation or anion size, indicating that the films of the grafted −COOH and −NH 2 layers act as good networks to support the IL, as illustrated in the left-bottom corners of Figure e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The third layer on the Au–NH 2 surface is also composed of the “cation–anion” pairs and so on. The difference in cation and anion layers formed closest to the Au–COOH and Au–NH 2 surfaces is due to their completely different interaction energies: the cation–COOH interaction energy is stronger than cation–NH 2 , while that is weaker for anion–COOH than anion–NH 2 . Note that due to the existence of these −COOH and −NH 2 functional groups, the detected ion layering thickness of the IL from the force–distance curves is not exactly equal to but very close to the theoretical cation or anion size, indicating that the films of the grafted −COOH and −NH 2 layers act as good networks to support the IL, as illustrated in the left-bottom corners of Figure e.…”
Section: Resultsmentioning
confidence: 92%
“…The difference in cation and anion layers formed closest to the Au−COOH and Au−NH 2 surfaces is due to their completely different interaction energies: the cation− COOH interaction energy is stronger than cation−NH 2 , while that is weaker for anion−COOH than anion−NH 2 . 56 Note that due to the existence of these −COOH and −NH 2 functional groups, the detected ion layering thickness of the IL from the force−distance curves is not exactly equal to but very close to the theoretical cation or anion size, indicating that the films of the grafted −COOH and −NH 2 layers act as good networks to support the IL, as illustrated in the left-bottom corners of Figure 4e. Previous studies revealed that the number of layering structures decreases with increasing molecular flexibility for conventional molecular liquids, as flexible molecules can pack effectively without layering.…”
Section: ■ Introductionmentioning
confidence: 90%
“…Additionally, it should be emphasized that intermediate organic matter may be formed during the sensing process and then adsorbed on the sensing layer. In this scenario, Pt would serve as a good catalyst for disrupting C–C bonds by deconstructing these intermediate species and promoting their faster desorption. , …”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, Pt would serve as a good catalyst for disrupting C−C bonds by deconstructing these intermediate species and promoting their faster desorption. 49,51 ■…”
Section: Synthesis Of Pure In 2 O 3 Hollow Microspheresmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are widely used as additives and solvents in industry and daily life. Most VOCs are toxic, carcinogenic, and combustible, seriously threatening human health and safety. Therefore, the detection of VOCs in the atmosphere is essential. Organic semiconductors (OS) have recently received increasing attention in gas sensors because of their potential applications in flexible and wearable electronics. In addition, organic semiconductors are genius for VOC gas-sensing applications because the precise organic synthesis can tailor functional groups for the specific binding of VOC analytes, leading to the prospect of simplifying gas sensors with enhanced responsivity and selectivity …”
Section: Introductionmentioning
confidence: 99%